2002
DOI: 10.1016/s1567-1356(02)00128-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of basidiomycetous yeasts: a comparison of large subunit D1/D2 and internal transcribed spacer rDNA regions

Abstract: Basidiomycetous yeasts in the Urediniomycetes and Hymenomycetes were examined by sequence analysis in two ribosomal DNA regions: the D1/D2 variable domains at the 5' end of the large subunit rRNA gene (D1/D2) and the internal transcribed spacers (ITS) 1 and 2. Four major lineages were recognized in each class: Microbotryum, Sporidiobolus, Erythrobasidium and Agaricostilbum in the Urediniomycetes; Tremellales, Trichosporonales, Filobasidiales and Cystofilobasidiales in the Hymenomycetes. Bootstrap support for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
192
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(202 citation statements)
references
References 0 publications
8
192
1
1
Order By: Relevance
“…The difference between these isolates and the eight Malassezia species exceeded that generally observed between species (Scorzetti et al, 2002). Phylogenetic analysis of 26S rDNA sequences from these isolates showed that they were conspecific and were clearly distinct from the other eight Malassezia species, although they were related closely to M. dermatis and M. sympodialis (Fig.…”
mentioning
confidence: 76%
“…The difference between these isolates and the eight Malassezia species exceeded that generally observed between species (Scorzetti et al, 2002). Phylogenetic analysis of 26S rDNA sequences from these isolates showed that they were conspecific and were clearly distinct from the other eight Malassezia species, although they were related closely to M. dermatis and M. sympodialis (Fig.…”
mentioning
confidence: 76%
“…For identification, the BioloMICS programm provided by Dr. V. Robert (Centraalbureau voor Schimmelcultures (CBS), Utrecht, The Netherlands) was used; it is available on internet page: www.cbs.knaw.nl . Identification of some Trichosporon strains and the Cryptococcus strain was confirmed by nuclear base sequencing of the D1D2 and ITS regions of 26S ribosomal DNA (Fell et al 2000;Scorzetti et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of isolated strains was made by sequences of the D1/D2 domains of the rDNA (Fell et al, 2000;Scorzetti et al, 2002) …”
Section: Yeast Identificationmentioning
confidence: 99%